From Metrics to Action: A Framework for Identifying Limiting Factors, Key Causes, and Possible Solutions in Food-Energy-Water Security - Schmidt, Jennifer I.; Huntington, Henry P.; Whitney, Erin; Huang, Daisy; Wies, Richard; Aggarwal, Srijan (Frontiers in Climate, 2022)
Food, energy, and water (FEW) security require adequate quantities and forms of each resource, conditions that are threatened by climate change and other factors. Assessing FEW security is important, and needs to be understood in the context of multiple factors. Existing frameworks make it hard to disentangle the contributors to FEW insecurity and to determine where best to expend efforts on short- and long-term solutions. We identified four consistent components of FEW security (availability, access, preference, quality). This framework provides detailed and nuanced insights into factors that limit or bolster security in each of the three sectors. The integrated framework identifies proximate and ultimate underlying causes of deficiencies in each security component providing opportunities to identify short and long term solutions.